Effective design and operation strategy of renewable cooling and heating system for building application in hot-humid climate. (February 2017) - Fong, K.F.; Lee, C.K.; Zhao, T.F.
Highlights: A renewable cooling and heating system was established to tackle high cooling demand. Solar energy was used in absorption cooling and water heating. Ground source was utilized by high-temperature chiller for radiant cooling. Appropriate year-round control and operation schemes were adopted. 44.4% annual primary energy saving for office building in hot-humid climate. Abstract: The utilization of renewable energy sources is commonly constrained by the building form and the site environment particularly in a densely-populated city which limits the space available to install the respective facilities. The hybrid use of solar and geothermal energy helps improve the situation as the roof and the ground can be fully utilized. A renewable cooling and heating system (RCHS) was therefore investigated based on this approach when applied to a three-storey office building in sub-tropical climate. Solar energy was used in absorption cooling and water heating while ground source was utilized by a high-temperature chiller for radiant cooling. Appropriate control and operation schemes were adopted for the ground-coupled radiant cooling system according to the ambient conditions in order to minimize the system energy demand. By performing dynamic system simulations using TRNSYS, the year-round performances of RCHS were thoroughly evaluated under different design factors including radiant panel type, ground thermal conductivity, borehole length and water heating demand. It was found that the RCHS was effective to tackle the high cooling demand for building in the hot-humid climate, with 44.4% annual primary energy saving against the conventional system.